Dystonia: phenomenology - LeDoux, Mark S. (Parkinsonism Relat Disord, 2012)
In 1984, dystonia was defined by an ad hoc committee of the Dystonia Medical Research Foundation as a syndrome of involuntary, sustained muscle contractions affecting one or more sites of the body, frequently causing twisting and repetitive movements, or abnormal postures. In 2011, dystonia remains a purely clinical diagnosis. Primary dystonia includes syndromes in which dystonia is the sole phenotypic manifestation with the exception that tremor can be present as well. Primary dystonias are typically mobile and may show task specificity. Fixed dystonias are often psychogenic or associated with complex regional pain syndrome. Fixed dystonia may also be the terminal consequence of long-standing, inadequately-treated, severe appendicular or cervical dystonia. The vast majority of primary dystonias have their onset in adults. Late-onset, primary, focal dystonia, particularly blepharospasm, may spread to affect other anatomical segments. Patients with focal dystonia may also exhibit spontaneous remissions that last for years. Although sensory tricks are commonly reported by patients with primary dystonia, they have also been described in subjects with secondary dystonia. Another important sensory aspect of dystonia is pain which is relatively common in cervical dystonia but also reported by many patients with masticatory dystonia, hand–forearm dystonia and blepharospasm. In conclusion, “dystonia” can be used to delimit a clinical sign or loosely define a neuropsychiatric sensorimotor syndrome.